Digital Learning Strategies to Enhance Student Engagement in Higher Education - Anthony Berry; Ellena Anastasia (Jipmor: Jurnal Ilmu Pendidikan Dan Humaniora, 2026)
This study investigates the effectiveness of digital learning strategies in improving student engagement in higher education, with particular emphasis on the integration of interactive multimedia, learning analytics, and collaborative online tools. The increasing use of digital platforms in university environments has created opportunities for more adaptive, personalized, and student-centered learning experiences. This study employed a mixed-method approach, combining quantitative survey data collected from 215 undergraduate students with qualitative thematic analysis of their learning experiences. The findings indicate that the implementation of digital learning strategies positively enhanced students' behavioral, emotional, and cognitive engagement. Students reported higher levels of motivation and participation when learning activities incorporated interactive multimedia, visual content, simulations, and engaging digital tasks. Learning analytics were perceived as useful for monitoring academic progress, identifying learning difficulties, and encouraging students to develop greater self-regulation. Meanwhile, collaborative online tools facilitated peer interaction, knowledge sharing, discussion, and collaborative problem-solving. Despite these benefits, several challenges were identified, including digital fatigue, unequal levels of digital competence, technical difficulties, and inconsistencies in digital infrastructure. These challenges indicate that the effectiveness of digital learning depends not only on the availability of technology but also on appropriate pedagogical implementation and institutional support. The study concludes that intentional digital pedagogical design, continuous instructor professional development, and adequate digital infrastructure are essential for maximizing the potential of technology-enhanced learning and promoting meaningful student engagement in higher education